Evolution of Monetary Policy Instruments in Russia - Balino, Tomas (IMF Working Papers; Working Paper ;, 1997)
This paper analyzes the evolution of monetary policy in Russia, focusing on the period January 1992-December 1995. Special attention is given to the role of monetary policy instruments. Initially, policy was completely dominated by flows of credit from the Central Bank of the Russian Federation (CBR) to the budget, to enterprises, and to other republics in the ruble area. Over time these flows have been reduced and indirect monetary instruments have become key elements of monetary policy implementation.